Erasmus Syndrome: An Underrecognized Entity - Magalhães, Ana (2022)
We present a case of a 33-year-old male who worked as a plumber and a locksmith. The patient presented with diffuse myalgia and asthenia, skin sclerosis and puffy fingers, Raynaud’s phenomenon, exertional dyspnea and erectile dysfunction. The presence of specific autoantibodies enabled the diagnosis of systemic sclerosis. Chest-computed tomography revealed upper lobe consolidation. After extensive evaluation, the multidisciplinary interstitial lung disease team concluded that the patient also had advanced silicosis. After a year, there was significant clinical, radiologic, and functional deterioration of the lung disease. The patient was referred for lung transplant. Silica inhalation is the cause of silicosis but is also implicated in the development of systemic sclerosis (Erasmus syndrome). Although they share a common risk factor, it is rare to find both diseases co-existing. We present this case of a young patient where both diseases presented aggressively in order to raise awareness to this association.